Effect of different curing modes on the degree of conversion and the microhardness of different composite restorations - Reem Ali Ajaj; Mohammed Khalil Yousef; Abeer Ibrahim Abo El Naga (Wolters Kluwer Medknow Publications, 2015)
Introduction: This study aims to evaluate the effects of different curing units and modes on the degree of conversion (DC) and microhardness (MH) of two different resin composites [ESTELITE ∑ QUICK (EQ), and Z350 XT (Z3)]. Materials and Methods: One hundred (100) discs of each tested material were made and divided into two subgroups (n = 50) according to the discs' dimensions: 5 mm diameter × 2 mm thickness, and 2 mm diameter × 2 mm thickness. Each subgroup was further subdivided into the following five classes (n = 10): I) cured with halogen light curing-unit; II) cured with light-emitting diode (LED) unit; III) cured with argon laser; IV) cured with halogen light-curing unit for 5 s, 10 s rest followed by 20 s curing; and V) cured with halogen light-curing unit for 10 s, then 10 s rest, followed by 10 s curing. The first subgroup was tested for MH using the Vickers Microhardness tester and the second subgroup was tested for DC using Fourier transform infrared spectroscopy (FTIR). Data were statistically analyzed using two-way analysis of variance (ANOVA) and Tukey's post hoc test P < 0.05. Results: Specimens in class IV showed the highest mean DC and MH, followed by class III, then class II. Class I showed significantly lower mean values for both DC and MH. On the other hand, Z3 showed statistically significantly higher mean DC and MH than EQ. Conclusion: Although the two tested composites did not perform similarly under the test conditions, curing with halogen unit for 5 s, then 10 s rest, followed by 10 s curing improved the DC and the MH of both the tested materials.